The past and future of NHS waiting lists in England - Max Warner; Ben Zaranko (Institute for Fiscal Studies (IFS), 2024)
NHS waiting lists are likely to be a key issue in the forthcoming general election. The current government has made cutting NHS waiting lists one of its key priorities, while one of the Labour party's five national missions is to "get the NHS back on its feet", including by cutting waiting times. In this IFS pre-election briefing, we outline what has happened to NHS waiting lists (in England, given that health is a devolved responsibility) over the last 17 years - the period for which consistent data are available - and present new scenarios of what could happen to waiting lists over the years to come. We focus on the elective waiting list - the list of people waiting for pre-planned hospital treatment and outpatient appointments. This is what most people mean when they talk about NHS waiting lists, but we also consider a range of other NHS waiting lists and waiting times. Alongside this report, we have updated our interactive online tool that allows you to produce waiting list scenarios under your own assumptions.
Keywords: 330; Health and social care; Election 2024; Health; Healthcare; NHS